2015
DOI: 10.5573/jsts.2015.15.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Current Spreading in GaN-based Light-emitting Diodes Using ITO Spreading Pad

Abstract: Abstract-In conventional LEDs, a mesa-structure is usually used and it causes the current to be overcrowded in a specific region. We propose a novel structure of GaN-based LED to overcome this problem. In order to distribute the current in an active region, a spreading pad is inserted at the p-type region in the GaN based LED device. The inserted spreading pad helps the current flow because it is more conductive than the p-type GaN layer. By performing electrical and optical simulations, the effects of the spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, many structural, physical, and thermo-electrical hurdles remain to be addressed before GaN-based micro-LED displays can become an effective solution. First, the lighting efficiency of highly scaled GaN microstructures is severely limited by current crowding and constrained current spreading [12][13][14][15]. Many previous studies have reported a drastic lowering of internal quantum efficiency as the GaN device scales below 50 µm pitch [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, many structural, physical, and thermo-electrical hurdles remain to be addressed before GaN-based micro-LED displays can become an effective solution. First, the lighting efficiency of highly scaled GaN microstructures is severely limited by current crowding and constrained current spreading [12][13][14][15]. Many previous studies have reported a drastic lowering of internal quantum efficiency as the GaN device scales below 50 µm pitch [16][17][18].…”
Section: Introductionmentioning
confidence: 99%